Sentence Patterns Which Represent Past, Present, and Future Event: A Case Study of Female Students at International Islamic Boarding School KH. Mas Mansur of Muhammadiyah University of Surakarta - Arifah, Siti; , Prof. Dr. Endang Fauziati, M. Hum; , Nur Hayati, M. Pd (2015)
SITI ARIFAH. A320100210. SENTENCE PATTERNS WHICH REPRESENT PAST, PRESENT, AND FUTURE EVENT: A CASE STUDY OF FEMALE STUDENTS AT INTERNATIONAL ISLAMIC BOARDING SCHOOL KH. MAS MANSUR OF MUHAMMADIYAH UNIVERSITY OF SURAKARTA. RESEARCH PAPER. 2015. The objective of the study is to describe sentence patterns which represent past, present, and future event, a case study of female students of International Islamic Boarding School KH. Mas Mansur of Muhammadiyah University of Surakarta. This study is qualitative research. The data are taken from all interlanguage systems which represent past, present, and future event made by the students in the form of English composition. The technique for collecting data is called documentation which are generated into three parts: (1) Collecting the data in the form of text containing interlanguage system (2) Identifying the English composition produced by the students by reading and marking the interlanguage system (3) Documenting the interlanguage system. The technique for analyzing data are classifying and describing the interlanguage system which represent past, present, and future event. The result of the study is the researcher found 19 types of interlanguage systems which represent past, present, and future event. The researcher found five types of interlanguage systems which represent past event, nine types of interlanguage system which represent present event, and five types of interlanguage systems which represent future event. Interlanguage system rises up as the the result off less understanding of English rule and it is because of the influence of native and target language. Keywords: Interlanguage system, university students, English composition, past, present, future.